Analisis Metode Penyampaian Pesan Mitigasi Bencana Pada Anak Disabilitas (Studi Kasus Edukasi Mitigasi Bencana Melalui Senam Mitigasi Bencana Gempa Kepada Siswa SLBN 1 Kota Padang) - Muhammad Zaki; Emeraldy Chatra; Sarmiati . (CV. ITTC INDONESIA, 2025)
Persons with disabilities, including individuals with intellectual disabilities, are among the most vulnerable groups during disasters, particularly earthquakes. This vulnerability is caused by intellectual limitations and barriers in comprehending information, including disaster mitigation messages. One disaster mitigation learning innovation developed at SLBN 1 Kota Padang is earthquake disaster mitigation gymnastics, which is based on songs and movements as an inclusive communication medium for students with intellectual disabilities. This study aims to analyze the role of interpersonal communication and the accuracy of disaster mitigation message delivery methods through earthquake disaster mitigation gymnastics. The research employed a qualitative method with a case study approach and collected through in-depth interviews, observation, and documentation, and analyzed using the Multimodal Interaction Analysis (MIA) framework. The findings show that delivering disaster mitigation messages through song- and movement-based mitigation gymnastics can enhance students’ understanding of earthquake safety procedures. Interpersonal communication approaches were applied in creating gymnastics movements that engaged the imaginative capacity of students with intellectual disabilities, as well as in reinforcing movement messages during class sessions. The gymnastics integrates various modes of communication verbal, visual, auditory, and kinesthetic in line with the principles of inclusive communication and the MIA framework. It also aligns with disaster mitigation communication principles, including customer focus, leadership commitment, inclusive policies, situational awareness, and media collaboration. Furthermore, the method is consistent with the frameworks of the Safe Schools/Madrasah from Disasters (SMAB) and Safe Education Units (SPAB), as well as national regulations on disaster education for vulnerable groups. Alignment is also found with the 3B method from ASB, WOHM, and the BNPB Pocket Book, including 3rd Pillar on Communication, Information, and Education (KIE) media. Delivering disaster mitigation messages through disaster mitigation gymnastics can therefore be recommended as an adaptive, enjoyable, and inclusive disaster education method.